2019
DOI: 10.1007/jhep02(2019)060
|View full text |Cite
|
Sign up to set email alerts
|

Argyres-Douglas theories, Painlevé II and quantum mechanics

Abstract: We show in details that the all order genus expansion of the two-cut Hermitian cubic matrix model reproduces the perturbative expansion of the H 1 Argyres-Douglas theory coupled to the Ω background. In the self-dual limit we use the Painlevé/gauge correspondence and we show that, after summing over all instanton sectors, the two-cut cubic matrix model computes the tau function of Painlevé II without taking any double scaling limit or adding any external fields. We decode such solution within the context of tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 80 publications
(226 reference statements)
1
45
0
Order By: Relevance
“…Further developments along these lines are reported in [7][8][9][10][11][12][13]. This correspondence has been then broadened to the case of q-difference Painlevé equations, q-Virasoro algebra [14][15][16][17][18][19] and five dimensional N = 1 gauge theories and nonperturbative topological strings [20][21][22][23][24]. The four-dimensional theories in question can be seen as arising as the world-volume theories of stacks of M5 branes wrapped around a punctured Riemann surface C g,n described by the compactification of the relevant 6d N = (0, 2) superconformal field theory [25].…”
Section: Contentsmentioning
confidence: 99%
“…Further developments along these lines are reported in [7][8][9][10][11][12][13]. This correspondence has been then broadened to the case of q-difference Painlevé equations, q-Virasoro algebra [14][15][16][17][18][19] and five dimensional N = 1 gauge theories and nonperturbative topological strings [20][21][22][23][24]. The four-dimensional theories in question can be seen as arising as the world-volume theories of stacks of M5 branes wrapped around a punctured Riemann surface C g,n described by the compactification of the relevant 6d N = (0, 2) superconformal field theory [25].…”
Section: Contentsmentioning
confidence: 99%
“…Indeed, an attempt to compute the partition function of AD theories as Liouville irregular conformal blocks was partially studied in [30,31]. 4 Finally, nice matrix model descriptions of this relation between AD theories and Painlevé equations have been studied in [37][38][39]. 5 In this paper, we extend the irregular conformal block approach to various directions, focusing on the (A 1 , A 3 ) and (A 1 , D 4 ) AD theories.…”
Section: Introductionmentioning
confidence: 99%
“…In this reference, the (A 1 , A 3 ) theory is called the H 1 Argyres-Douglas theory 28. While the D 3 is not explicitly written in[15], the authors of[37] evaluated it using a nice matrix model description as shown in Eq. (3.23) of[37].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Observe that, taking into account (40), the rescaling by γ −1 of the argument of the τ function in (46) is the simplest way of cancelling the logarithmic term −1/16 log(x/γ) in the limit x → ∞ and recovering the prediction of the Szegő theorem (8). Note also that, in virtue of (42), the terms in the second line of the expression (46) are invariant under the transformation (41).…”
Section: Exact Results For γ = 1 and Conjectures For γ =mentioning
confidence: 99%